ANALYSIS OF THE INFLUENCE OF SOCIAL AND ECONOMIC INFRASTRUCTURE ON THE DYNAMICS OF ECONOMIC GROWTH IN WEST JAVA PROVINCE FOR THE PERIOD 2020 – 2024 - Siti Naeni Nur Khaeni; Hastarini Dwi Atmanti (Journal of Development Economics and Digitalization, Tourism Economics, 2025)
This study analyzes the influence of social and economic infrastructure on the dynamics of economic growth in West Java Province for the 2020–2024 period. Using panel data regression with a Fixed Effect Model, the research examines the impact of road length, access to clean water, health personnel, and literacy rates on regional economic growth, measured by GRDP per capita. The results show that access to clean water and the number of health personnel have a significant positive effect on economic growth, while road length and literacy rates do not have a statistically significant impact. These findings highlight the crucial role of health and clean water infrastructure in supporting regional economic recovery and growth, especially in the post-pandemic context. The study recommends that policymakers prioritize investment in health and clean water infrastructure to achieve more inclusive and sustainable economic development in West Java.